Bibliometrics analysis on the research status and trends of adult-onset Still’s disease: 1921-2021 - Qin, Aining; Sun, Jing; Gao, Chao; Li, Chunying (Frontiers in Immunology, 2022)
Objectives The aim of this research is to discuss the research status, hotspots, frontiers and development trends in the field of adult-onset Still’s disease (AOSD) based on bibliometrics and visual analysis by CiteSpace software. Methods The relevant research articles on AOSD from 1921 to 2021 were retrieved from the Scopus database. CiteSpace software was used to form a visual knowledge map and conduct analysis for the countries/regions, journals, authors, keywords, clusters, research hotspots and frontiers of the included articles. Results There were 2,373 articles included, and the number of articles published during 1921-2021 is increasing. The country with the highest number of articles published was Japan (355, 14.96%), followed by the United States (329, 13.86%) and France (215, 9.06%). The author with the highest number of publications is Ansell, Barbara M. (30, 1.26%), and the author with the highest co-citation frequency is Yamaguchi, Masaya (703). Clinical Rheumatology is the journal with the highest publication frequency. The top five cluster groups were “joint”, “differential diagnosis”, “prednisolone”, “methotrexate” and “macrophage activation syndrome”. The diagnosis, treatment and pathogenesis of AOSD form the main research fields, and prognosis and complications are the research hotspots and trends. Conclusions The global research field in AOSD has expanded in the past 100 years. The complications and new pathogenesis of AOSD are hotspots in this field and need further study in the future.